Clinical and economic feasibility study of the use of vitamin and mineral complexes in case of miscarriage - N A Kurmacheva; E V Verizhnikova; G Yu Chernyshova; Yu V Chernenkov; O M Kharitonova (IP Berlin A.V., 2017)
The purpose: to conduct a pharmacoeconomic analysis of two schemes of vitamin-mineral drugs in the peri-gestation period in women with habitual miscarriage and polymorphisms of folate cycle genes, giving birth to full-term children. Materials and methods: the cost-effectiveness of vitamin-mineral preparations in two groups of women was calculated. Patients of the 1st group (n=60) received pregravidno and during pregnancy a vitamin-mineral complex containing in one tablet metafolin, other vitamins of group B, vitamins C, E, PP and iodine (150 mcg) in physiological dosages, and also 200 mg of docosahexaenoic acid in a capsule intended for use from the 13th week until the end of pregnancy. Women of the 2nd group (n=54) took high doses of synthetic folic acid, vitamins B6 and B12 as part of two vitamin and mineral preparations during the pregravid preparation and gestational period. During pregnancy, the patients of both groups received an additional 100 mcg of potassium iodide daily. Results: in the 1st group, the cost-effectiveness ratio was 1.6 times lower and the clinical efficacy was significantly higher than in the 2nd group and consisted in a significant decrease in the incidence of preeclampsia, placental insufficiency, intrauterine fetal hypoxia, complications in the time of delivery, as well as the diseases in their children in the early neonatal period (1.5-3.9 times, p